(untitled) (Veterinary Science, 2017)
The immune response against infectious agents involves a complex interaction among different cells types and their produce that culminate with disease resolution or death. Mastitis continues to be a high incidence and costly disease in the dairy industry. The animal susceptibility to the disease changes during the milk production period of the dairy cow, therefore the objective of this review is to describe the immune and non immune mechanisms known so far